2020
DOI: 10.1111/ijtd.12199
|View full text |Cite
|
Sign up to set email alerts
|

Human resource development practices supporting creativity in Finnish growth organizations

Abstract: Creativity can be enhanced through appropriate Human Resource Development (HRD) practices that support employees' learning and competence development. The aim of this study is to increase our understanding of HRD practices that enhance creativity in Finnish growth companies. To achieve this aim, we searched for creativity requirements based on employees' experiences expressed in interviews, and we studied HRD practices used in organizations that respond to the requirements of creativity. We gathered 98 intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
2
19
0
2
Order By: Relevance
“…The findings of this research can be adopted and practiced in Thai company to promote innovative behavior in organizations. This study confirmed that all proposed factors of innovative behavior are important in Thailand context and the results of this research are consistent with prior researches conducted in other countries (Collin, Lemmetty, & Riivari, 2020;Walker & Derbyshire, 2020) as well as mentioned in table 1. The internal factors contain knowledge sharing (KS), self-efficacy (SE), problem-solving capacity (PS), collaborative skill (CS) and the external factors contain innovation culture (IC), organizational supportiveness (OS), learning culture (LC), and executive leadership (EL).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this research can be adopted and practiced in Thai company to promote innovative behavior in organizations. This study confirmed that all proposed factors of innovative behavior are important in Thailand context and the results of this research are consistent with prior researches conducted in other countries (Collin, Lemmetty, & Riivari, 2020;Walker & Derbyshire, 2020) as well as mentioned in table 1. The internal factors contain knowledge sharing (KS), self-efficacy (SE), problem-solving capacity (PS), collaborative skill (CS) and the external factors contain innovation culture (IC), organizational supportiveness (OS), learning culture (LC), and executive leadership (EL).…”
Section: Discussionsupporting
confidence: 91%
“…First, the definition focuses on employees' actual behaviour (Raemdonck et al, 2014), also coined participation in learning activities (e.g., Grosemans, Smet, et al, 2020) or in development practices (Collin et al, 2020). This behaviour is at the core of informal learning when seen from a process perspective: Triggers or resources facilitate the engagement in informal workrelated learning behaviours and this leads to outcomes (Kyndt et al, 2016).…”
Section: Formal and Informal Work-related Learningmentioning
confidence: 99%
“…Furthermore, stakeholders in this context are the people in the organisation who have a keen interest in the HRD interventions and for whom support is needed for these interventions to be effective (Noe, 2020). Collin et al (2020) found that clearly articulated supervisory roles and welldescribed structures are fundamental to HCD practices that lead to more employee creativity in the workplace. If the relationship between the key role players in HCD (i.e.…”
Section: Human Capital Development As Key Performance Area Of Line Ma...mentioning
confidence: 99%